Schizophrenia Increases Variability of the Central Antioxidant System: A Meta-Analysis of Variance From MRS Studies of Glutathione - Palaniyappan, Lena; Sabesan, Priyadharshini; Li, Xuan; Luo, Qiang (Frontiers in Psychiatry, 2021)
Patients with schizophrenia diverge in their clinical trajectories. Such diverge outcomes may result from the resilience provided by antioxidant response system centered on glutathione (GSH). Proton Magnetic Resonance Spectroscopy (1H-MRS) has enabled the precise in vivo measurement of intracortical GSH; but individual studies report highly variable results even when GSH levels are measured from the same brain region. This inconsistency could be due to the presence of distinct subgroups of schizophrenia with varying GSH-levels. At present, we do not know if schizophrenia increases the interindividual variability of intracortical GSH relative to matched healthy individuals. We reviewed all 1H-MRS GSH studies in schizophrenia focused on the Anterior Cingulate Cortex published until August 2021. We estimated the relative variability of ACC GSH levels in patients compared to control groups using the variability ratio (VR) and coefficient of variation ratio (CVR). The presence of schizophrenia significantly increases the variability of intracortical GSH in the ACC (logVR = 0.12; 95% CI: 0.03–0.21; log CVR = 0.15; 95% CI = 0.06–0.23). Insofar as increased within-group variability (heterogeneity) could result from the existence of subtypes, our results call for a careful examination of intracortical GSH distribution in schizophrenia to seek redox-deficient and redox-sufficient subgroups. An increase in GSH variability among patients also indicate that the within-group predictability of adaptive response to oxidative stress may be lower in schizophrenia. Uncovering the origins of this illness-related reduction in the redox system stability may provide novel treatment targets in schizophrenia.